Efficacy and safety of a novel mucoadhesive clobetasol patch for treatment of erosive oral lichen planus: A phase 2 randomized clinical trial. (13th January 2022) - Brennan, Michael T.; Madsen, Lars Siim; Saunders, Deborah P.; Napenas, Joel J.; McCreary, Christine; Ni Riordain, Richeal; Pedersen, Anne Marie Lynge; Fedele, Stefano; Cook, Richard J.; Abdelsayed, Rafik; Llopiz, Maria T.; Sankar, Vidya; et al.
Abstract: Background: Oral lichen planus (OLP) is a chronic inflammatory disorder of the oral mucosa. Currently there is no approved treatment for OLP. We report on the efficacy and safety of a novel mucoadhesive clobetasol patch (Rivelin ® ‐CLO) for the treatment of OLP. Methods: Patients with confirmed OLP and measurable symptomatic ulcer(s) participated in a randomized, double‐blind, placebo‐controlled, multicenter clinical trial testing a novel mucoadhesive clobetasol patch (Rivelin ® ‐CLO) in OLP across Europe, Canada, and the United States. Patients were randomized to placebo (nonmedicated), 1, 5, 20 µg Clobetasol/patch, twice daily, for 4 weeks. The primary endpoint was change in total ulcer area compared to baseline. Secondary endpoints included improvement from baseline in pain, disease activity, and quality of life. Results: Data were analyzed and expressed as mean [SD]. One hundred thirty‐eight patients were included in the study; 99 females and 39 males, mean age was 61.1 [11.6] years. Statistical analyses revealed that treatment with 20‐μg Rivelin ® ‐CLO patches demonstrated significant improvement with ulcer area ( p  = 0.047), symptom severity ( p  = 0.001), disease activity ( p  = 0.022), pain ( p  = 0.012), and quality of life ( p  = 0.003) as compared with placebo. Improvement in OLP symptoms from beginning to the end of the study was reported as very much better (best rating) in the 20‐µg group (25/32) patients compared to the placebo group (11/30), ( p  = 0.012). Adverse events were mild/moderate. Candidiasis incidence was low (2%). Conclusions: Rivelin ® ‐CLO patches were superior to placebo demonstrating statistically significant, clinically relevant efficacy in objective and subjective improvement and, with a favorable safety profile.